A multicriteria approach to integrating occupational safety & health performance and industry systems productivity in the context of aging workforce: A case study. (August 2022) - Ortiz-Barrios, Miguel; Silvera-Natera, Esnela; Petrillo, Antonella; Gul, Muhammet; Yucesan, Melih
Highlights: Aging workforce represents one of the greatest challenges that mankind in the 21st century. A multicriteria approach to integrate OSHP and ISP in the context of AW is proposed. One of the most important results proven the importance of adjusting the workload as aging advances. The model can be an useful tool for policy and business decision-makers. Abstract: Aging represents one of the greatest challenges that mankind will have to face in the 21st century. In this regard, there is a need to deepen the technical and organizational aspects for rebalancing the job/employee relationship. Nevertheless, there are no robust approaches assisting decision-makers in the effective management of Occupational Safety & Health Performance (OSHP) and Industry Systems Productivity (ISP) convergence with a focus on Aging Workforce (AW). There is no single and unique solution. Therefore, in a win-to-win logic that favors the characteristic of the reference scenario, the aim of this paper is to propose a multicriteria approach to integrate OSHP and ISP in the context of AW. More specifically, Intuitionistic Fuzzy Analytic Hieararchy Process (IF-AHP) was used to elicit the criteria and sub-criteria under uncertainty considering degree of belongingness and non-belongingness. Decision Making Trial and Evaluation Laboratory (DEMATEL) was applied to evaluate the presence and strength of the interrelations and feedback among OSHP and ISP criteria and sub-criteria. Finally, Combined Compromise Solution (CoCoSo) was implemented to calculate a Working Suitability Index (WSI) per aging. Based on this index, interventions on each worker are proposed to underpin redesign of the company while to provide a flexible management propelling high performance in terms of OSHP and ISP. A real case study in Colombia is presented. The results revealed that Efficiency and Quality with 0.162 were found to be the most important factors in evaluating the performance of aging electrical engineers while Psychosocial risk and Occupational Safety w ere concluded to be the main drivers for a joint OSHP-ISP aging workforce management. The model can be an useful tool for policy and business decision-makers from the electrical sector and can be replicated with slight changes in other industries.